Isotopic signatures of magmatic fluids and seawater within silicic submarine volcanic deposits. (1st June 2022) - Mitchell, Samuel J.; Hudak, Michael R.; Bindeman, Ilya N.; Carey, Rebecca J.; McIntosh, Iona M.; Houghton, Bruce F.; Rubin, Kenneth H.
Abstract: Addressing questions of magma ascent, volcanic eruption dynamics, and volatile fluxes requires accurate measurement of magmatic water concentrations in volcanic glass. Glass in volcanic rocks in the deep-sea environment can experience rehydration (addition of external water) across a range of temperatures, and from different sources (e.g., seawater and hydrothermal fluids), which can lead to overestimation of magmatic-H2 O. This study used H and O isotopes (δD and δ 18 O) to identify sources of rehydration in pumice and lava from the deep-sea 2012 volcanic eruption of Havre volcano, Kermadec Arc, and from a variety of older (tens to thousands of years) silicic submarine deposits across the Izu-Bonin Arc and Lau Basin. We find that old seafloor pumices were rehydrated up to 6 wt.% H2 O by the diffusion of cold seawater over 100s to 1000s of years, and thus, enriched in δD, bulk-δ 18 O, and water-in-glass (wig) δ 18 O up to −30‰, +9‰ and −5‰ respectively. By contrast, the young Havre deposits exhibit a much wider range of both isotopic enrichment and depletion with δD = −50 to −120‰, δ 18 Obulk = +5.7 to +6.2‰, and δ 18 Owig  = −10 to +4‰, depending on the eruptive units. Using magmatic degassing and vapor δD-H2 O modeling, a volatile-melt δ 18 O-geothermometer, and previous textural studies of Havre 2012 deposits, we identify multiple high-temperature rehydration sources, timescales, and mechanisms. δD-depleted pumices were likely rehydrated by vapor co-existing in bubbles and vesicles at temperatures around and below the glass transition (320–670 °C) over timescales of a few minutes during clast cooling above the eruptive vent. Conversely, δD-enriched Havre pumice and lava from different deposits were most likely rehydrated by heated, δD-enriched seawater at glass temperatures > 100 °C. These results provide a natural confirmation of recent experimental findings, which tackle the fundamentals of H and O diffusion and isotope exchange in silicate materials at temperatures of 100–400 °C. Addressing the effects of rehydration, and thus accuracy of H2 O measurements, in volcanic glasses and crystals is important for improving our understanding of conduit processes during volcanic eruptions, and the kinetics of glass hydration and alteration.